2021
DOI: 10.1016/j.jebo.2021.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Do retail investors bite off more than they can chew? A close look at their return objectives

Abstract: Using information self-reported by retail investors in a risk-return profiling survey, we investigate the determinants of individual return objectives as well as the capacity of investors to reach them. Controlling for a large set of covariates, we provide empirical evidence that return objectives are related to subjective individual characteristics (such as financial literacy and risk tolerance), some sociodemographics (age, education), as well as recent past trading intensity. Retail investors with higher re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 90 publications
1
7
0
Order By: Relevance
“…Finally, D'Hondt, De Winne, and Merli (2021) showed that MiFID questionnaire answers provide useful information about retail investors return objectives. In fact, in the MiFID questionnaire of the second dataset, retail investors must self‐report their expected portfolios return.…”
Section: Mifid Questionnaires Data As a Tool For Financial Advisorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, D'Hondt, De Winne, and Merli (2021) showed that MiFID questionnaire answers provide useful information about retail investors return objectives. In fact, in the MiFID questionnaire of the second dataset, retail investors must self‐report their expected portfolios return.…”
Section: Mifid Questionnaires Data As a Tool For Financial Advisorsmentioning
confidence: 99%
“…Using past and actual investor stock portfolio returns, this paper investigates the determinants of individual return objectives as well as the capacity of investors to achieve them. D'Hondt, De Winne, and Merli (2021) found that return objectives are related to individual characteristics, such as subjective financial literacy and risk tolerance, sociodemographics and recent past trading intensity.…”
Section: Mifid Questionnaires Data As a Tool For Financial Advisorsmentioning
confidence: 99%
See 3 more Smart Citations